A novel system of biomass-based hydrogen production by combining steam bio-oil reforming and chemical looping process. (15th June 2020) - Situmorang, Yohanes Andre; Zhao, Zhongkai; An, Ping; Yu, Tao; Rizkiana, Jenny; Abudula, Abuliti; Guan, Guoqing
Graphical abstract: Highlights: A novel system for hydrogen production from biomass is proposed and simulated. The system consists of pyrolysis/bio-oil reforming/biochar chemical looping processes. Waste heat circulation is designed and applied to reach an auto-thermal system. This system has higher hydrogen production efficiency than other systems. This system produces positive net power besides hydrogen production. Abstract: Biomass to hydrogen is becoming a promising way to produce clean energy with zero or even negative carbon emission. In this study, a novel system containing a biomass pyrolysis process, a catalytic steam reforming of bio-oil process, a chemical looping unit using biochar as the reducing agent and other auxiliary processes including H2 separation and thermal energy circulation processes for hydrogen production is proposed and simulated based on the previous studies. While, a waste heat recovery system is recommended for energy recuperation to make the entire system become auto-thermal. The effects of steam to carbon ratio in the catalytic steam reforming reaction and temperatures at reducing and steam reactors in the chemical looping unit on the system performance are analyzed in details. Under the optimum condition in the proposed system, about 6.9 kg/h of hydrogen could be produced from 100 kg/h of wood biomass with 58.3 kW of net power. Compared with the biomass direct chemical looping process for H2 production, separating the bio-oil and biochar after the pyrolysis process and combining the steam bio-oil reforming process with the chemical looping unit using biochar for H2 production can increase H2 production efficiency from biomass by more than 50%. It is expected that this proposed system could be implemented in a practical application.